Mobile game app development – gamification on running - Chan, Jennifer Yi Ting (2017)
Despite the benefits of running, people may still be unmotivated to run regularly. By incorporating gaming elements into activities, people may be encouraged to participate and their engagement levels may be increased. When executed well, gamification helps to align the activity with intrinsic motivations of the players and attracts them to keep returning to the activity. Hence, the aim of this project is to encourage running through gamification. Based on foundations and concepts of gamification, a game prototype was developed to illustrate the basic game play and mechanics. However, further development and game planning will be required to engage real users in future.